Efeitos de peptídeos derivados da beta globina LVV-H6 e LVV-H7 sobre os comportamentos tipo-ansiedade e tipo-depressão, função cardíaca e vascular de ratos - Cruz, Kellen Rosa da (2019)
Hemorphins are peptides derived from the hemoglobin β-globin chain. LVV- hemorphine-6 and LVV-hemorphine-7 (LVVs) are bioactive hemorphins, which exhibit similar amino acid residue sequence, differing only by the amino acid Phenylalanine at the N-terminus of LVV-hemorphine-7. Both hemorphins reduce anxiety-like and depression-like behavior, the latter being promoted by LVV-h7, is oxytocin receptors dependent, but not the effect evoked by LVV-h6. In addition, the data in the literature about the cardiovascular effects evoked by LVV-h7 are controversial and there are no studies on the effects of LVV-h6 on this physiological system. Therefore, the objective of this study was to identify the mechanisms involved in behavioral effects and also to verify the effects on vasomotricity and cardiac function in the aorta artery and isolated heart of Wistar rats. The experimental protocols were carried out according to the norms of use of animals, under project approval by the committee of ethics and animal use of the UFG (Protocol of approval nº 090/14). The Elevated Pluz Maze (EPM) was used to evaluate the anxiety-like behavior and were then placed in the Open Field (OF) to evaluate locomotion. To evaluate the depression-like behavior, the Forced Swim test (FST) was used. The isolated vessel technique was used to evaluate vascular reactivity in thoracic aorta rings isolated and the Langendorff technique to evaluate heart function in heart i solated from Wistar rats. The anxiolytic-like effect of both hemorphins does not depend on the route of biosynthesis of catecholamines or the activation of opioid receptors. However, the antidepressant-like effect of LVVs was reversed by blockade of opioid receptors, indicating the activation of these receptors as a potential mechanism. Both LVVs similarly reduce perfusion pressure, maximal and minimum dP/dt and systolic and diastolic intraventricular pressure in heart isolated from rats, without promoting contraction or relaxation of aorta rings isolated from rats. Thus, although LVVs cause the same effects on anxiety-like and depression-like behavior, the underlying mechanisms are partially different, even with a substantial similarity in the primary structure of these hemorphins. In addition, LVVs act by decreasing cardiac function, in the evaluated parameters, in isolated heart of normotensive rats without affecting the vasomotricity of aorta rings isolated of normotensive rats.